2023
DOI: 10.21203/rs.3.rs-2565845/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Life history and population growth parameters of the rice weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae) fed on 10 rice cultivars and lines

Abstract: The rice weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae), is one of the most destructive pests of stored cereal grains globally. In this study, we evaluated the grain resistance of different rice cultivars (Anam, Gilar, Hashemi, Keshvari, Rash, and Tisa) and lines (8608, MN-7, TH-1, and TH-2) using life history and life table parameters of S. oryzae under laboratory conditions (28 ± 1°C, 70 ± 5% relative humidity, and complete darkness). The immature survival of S. oryzae decreased significantly when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…According to Majd-Marani et al (2023), the content of phenols and lipids in the food eaten by insects may also significantly impact development. Significant relationships between the development time, longevity, and fecundity of S. oryzae and the content of phenols in the tested grains reveal this factor's important role in the rice weevil's life cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Majd-Marani et al (2023), the content of phenols and lipids in the food eaten by insects may also significantly impact development. Significant relationships between the development time, longevity, and fecundity of S. oryzae and the content of phenols in the tested grains reveal this factor's important role in the rice weevil's life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of previous scientific studies, it appears that the impact of the content of fatty acids in grains on the development of insects, available information suggests that the fat content in most cereal plants plays an important role in shaping the storage stability of cereal products and may influence the feeding behaviour of S. granarius (Liu, 2011). The research of Majd-Marani et al (2023) correlation analysis showed that the content of glycogen and lipids in S. oryzae pupae has significant relationships with development time, fecundity, and longevity of adults. In research conducted by Nietupski et al (2021), no significant relationships were revealed between the level of individual fatty acids in grains of various wheat varieties and parameters related to the development of the grain weevil.…”
Section: Discussionmentioning
confidence: 99%